Neo-Growth in Future Post-Carbon Cities - Sirkka Heinonen (Tamkang University, 2026)
Ancient Greece had city-states – in 100 years we will have city-worlds. The global challenge of
urbanisation has been acerbated due to megatrends such as climate change, demographic change
(i.e. ageing of the population in industrialised countries, and increasing populations in developing
countries and new economies) globalisation and financial crises. The rise of megacities will speed
up urbanisation. The concepts and structures of new cities and the urban sprawl of existing cities has
been directly linked to energy, water, food, health and security issues. The consumption of fossil fuels
in construction, housing, transport and industry should be minimised and replaced with renewable
forms of energy. Future cities will also create a built environment that is based on a different logic than
today. Humans started to construct cities thousands of years ago, as shelter for survival and as centres
of housing, trading and recreation. In the future, cities will themselves be like organisms; sensitive and
responsive to interaction, self-constructing “cyburgs”. They are foreseen to emerge as self-sufficient
isles for energy, food, and comfort in the urban archipelago.